Hospital Accreditation Implementation Prerequisites - Alimohammad Mosadeghrad; Erfan Shakibaei (Tehran University of Medical Sciences, 2017)
Background: Accreditation is an appropriate strategy for improving the quality, safety and effectiveness of hospital services. Iran national hospital accreditation was initiated as a government and mandatory program in 2012. This study aimed to identify the prerequisites of hospital accreditation implementation in Tehran province hospitals.   Materials and Methods: This qualitative study was performed using semi-structured interviews with 72 managers in different level from 15 university, private, military, social security and charity hospitals in 2016. Hospitals were selected purposefully through Tehran province hospitals. Content analysis was used in order to data analysis.   Results: Pilot testing of standards before announcing to hospitals for implementation, education and training of hospital managers and employees on accreditation standards, providing required resources, allocating enough time for implementing the standards and providing incentives for implementing standards are the main hospital accreditation prerequisites. Absence of these prerequisites in accreditation implementation resulted in huge challenges for hospital managers and employees.   Conclusion: Providing the accreditation prerequisites for hospitals facilitates implementation of hospital accreditation in hospitals which in turn results in quality improvement, safety and hospital services effectiveness.